CORRELATIONS BETWEEN COACHING BEHAVIOR, MOTIVATIONAL CLIMATE AND INTRINSIC MOTIVATION IN CADET BASKETBALL PLAYERS - Miroljub Ivanović,; Uglješa Ivanović, (Sport Scientific And Practical Aspects, 2025)
Aim:The aim of this research is the empirical study of coach’s social contribution to intrinsic motivation of cadet basketball players. The research included the pertinent sample (N = 114) of participants from five basketball clubs from Valjevo. The average age of participants was 15,36 years. Methods: The following measuring instruments were used: The Leadership Scale for Sports questionnaire (LSS), Negative Coaching Behavior Questionnaire (UNPT), Perceived Motivational Climate in Sport Questionnaire (PMSCQ), and The Intrinsic Motivation Inventory (IMI). Results: The obtained results indicate that there are 2/3 of bivariate correlations between the examined variables in adolescent basketball population. The applied hierarchical analysis included the variables coach’s positive and negative actions in the first predictor group, and mastery-oriented motivational climate in the second. The regression equation accounted for 30% of the variability of the scores on the criterion variable intrinsic motivation, where coach’s negative actions are revealed as significant negative predictor variable, while the mastery-oriented motivational climate was a positive predictor of the criterion. Conclusion: The possible explanations and implications were discussed in this research. The obtained results indicate that the examined variables are relevant for understanding and predicting intrinsic motivation in adolescent basketball players